已知函数f(x)=
(1)求a,b,c,d的值; (2)求证:g(x)在R上是增函数. |
(1)因为函数f(x)=
,g(x)=ax3+cx2+bx+d都是奇函数,ax2+d+1 bx+c
所以f(-x)=-f(x),
∴
=-ax2+d+1 -bx+c ax2+d+1 bx+c
解得c=0…(1分)
由g(-x)=-g(x)可得-ax3+cx2-bx+d=-ax3-cx2-bx-d
∴d=0…(2分)
∴f(x)=
,g(x)=ax3+bxax2+1 bx
由f(1)=
=2得a=2b-1,…(3分)a+1 b
代入f(x)中得f(x)=
,(2b-1)x2+1 bx
∵f(2)=
<3,即4-8b-3 2b
<3,3 2b
∴
>1,所以b>0,由此可解得:0<b<3 2b
…(4分)3 2
考虑到a,b,c,d∈Z,所以b=1,所以a=2b-1=1,…(5分)
综上知:a=1,b=1,c=0,d=0.…(6分)
证明(2)∵a=1,b=1,c=0,d=0,所以函数g(x)=x3+x,
任取x1,x2∈R,且x1<x2,…(1分)
g(x2)-g(x1)=(x23-x13)+(x2-x1)=(x2-x1)(x22+x2x1+x12)+(x2-x1) =(x2-x1)[(x22+x2x1+
x12)+1 4
x12+1]=(x2-x1)[(x2+3 4
x1)2+1 2
x12+1]3 4
∵x2-x1>0,(x2+
x1)2+1 2
x12+1>0,(如中间没配方,则-2分)3 4
∴g(x2)>g(x1),
∴g(x)在R上是增函数.…(4分)